(untitled) (Prostor, 2022)
Public art plays a number of roles in the economic, social and cultural transformation of cities. The cultural policies of cities are significant for the interest in public art. The percent for art strategy as an important policy is one of the methods to promote public art in cities and finance artwork production. Many cities have been successfully implementing public art in their cultural policies. The cities of Chicago, Barcelona and Dublin can be mentioned as those which have different experiences in the implementation of this strategy. They can be taken as exemplars of cultural policies and public art strategies for the specific case of Izmir, Turkey. This article intends to discuss public art as part of cultural policies in Izmir, demonstrating how public art can find more space in the urban environment. In line with this purpose, the main question focuses on how the percent for art scheme can be applied as a method that ensures the realization of public art practices for Izmir. The resultant findings obtained from proposed models show that an alternative financial resource can be provided via the percent for art strategy in Izmir city. In the end, the percent for art program is believed to offer a range of opportunities which should increase the presence of public art in the city.